Cleavage of DNA containing 5-fluorocytosine or 5-fluorouracil by type II restriction endonucleases - Olszewska, Agata; Dadová, Jitka; Mačková, Michaela; Hocek, Michal (Bioorganic & medicinal chemistry, 2015)
A systematic study of the cleavage of DNA sequences containing 5-fluorocytosine or 5-fluorouracil by type II restriction endonucleases (REs) was performed and the results compared with the same sequences containing natural pyrimidine bases, uracil or 5-methylcytosine. The results show that some REs recognize fluorine as a hydrogen on cytosine and cleave the corresponding sequences where the presence of m5dC leads to blocking of the cleavage. However, on uracil, the same REs recognize the F as a methyl surrogate and cleave the sequences which are not cleaved if uracil is incorporated instead of thymine. These results are interesting for understanding the recognition of DNA sequences by REs and for manipulation of the specific DNA cutting.
Keywords: Fluorouracil; Flucytosine; flucytosin; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; DNA polymerase; štěpení DNA; Deoxyribonucleases, Type II Site-Specific; Modified nucleotides; Restriction endonucleases; Pyrimidine nucleosides; restrikční endonukleasy typu II; DNA; DNA Cleavage; fluoruracil